2012
DOI: 10.3174/ajnr.a3235
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Regional Gray Matter Volume in Patients with Chronic Obstructive Pulmonary Disease: A Voxel-Based Morphometry Study

Abstract: BACKGROUND AND PURPOSE:Decreased oxygen supply may cause neuronal damage in the brains of patients with COPD, which is manifested by clinical symptoms such as neuropsychological deficits and mood disorders. The aim of the present study was to investigate brain gray matter change in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 38 publications
5
57
2
Order By: Relevance
“…SFG=superior frontal gyrus, dmPFC=dorsomedial prefrontal cortex, Pre-SMA=pre-supplement motor area neuroimaging study also did not find any local WM volume reduction in the patients with COPD (Ryu et al 2013). Our findings are, at least partly, consistent with previous VBM studies, which reported gray matter volume reductions in prefrontal, temporal and motor cortices (Zhang et al 2012(Zhang et al , 2013. The present findings suggest most of the decreased gray matter volumes observed in VBM studies are likely to represent cortical thinning, although there may also be a component of cortical area reduction.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…SFG=superior frontal gyrus, dmPFC=dorsomedial prefrontal cortex, Pre-SMA=pre-supplement motor area neuroimaging study also did not find any local WM volume reduction in the patients with COPD (Ryu et al 2013). Our findings are, at least partly, consistent with previous VBM studies, which reported gray matter volume reductions in prefrontal, temporal and motor cortices (Zhang et al 2012(Zhang et al , 2013. The present findings suggest most of the decreased gray matter volumes observed in VBM studies are likely to represent cortical thinning, although there may also be a component of cortical area reduction.…”
Section: Discussionsupporting
confidence: 94%
“…Surface-based measures of CTh, SA and LGI provide more precise neurobiological representations, and has been shown to be more sensitive in capturing subtle, previously undetected anatomical alterations (Jiao et al 2010;Pereira et al 2012;Kelly et al 2013), particularly in deep sulcal regions (Lerch and Evans 2005). In the present study, novel regions were discovered primary in highly convoluted parietal cortex besides those detected by traditional volumetric methods in previous studies (Zhang et al 2012(Zhang et al , 2013. Damage in DLPFC has been recurred and identified as an important area in this study which contributes notably to the visuospatial deficits.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Neuroimaging studies showed there are signiicantly lowered gray mater volumes in several brain regions as hippocamp [7], limbic and paralimbic structures [77], precuneus, bilateral calcarine, right superior temporal gyrus/middle temporal gyrus, bilateral fusiform, right inferior parietal lobule [78], cingulate and amygdala [8], dorsolateral prefrontal cortex [77] etc., evidenced by diferent neuroimaging techniques based on magnetic resonance imaging (MRI). Performance accuracy has increased by introducing voxel-based morphometry analysis also based on MRI.…”
Section: Clinical Consequences Of An Afected Cognition; Measure Methodsmentioning
confidence: 99%
“…The newborns with congenital heart disease (45,46). For other diseases, changes have been found in adult brain for type 2 diabetes (47-50), asthma (51,52), and chronic obstructive pulmonary disease (53)(54)(55). Improvements in diagnostic methods will make it possible to establish changes during early life.…”
Section: The Role Of Hypoxia In the Neurogenesis Stimulationmentioning
confidence: 99%